PERTANGGUNGJAWABAN HUKUM DALAM DUGAAN TINDAK PIDANA PERJUDIAN YANG BERKEDOK TRADING BINOMO DALAM PERSPEKTIF UU ITE - Divea Aura Meisyadina (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Binomo has become a topic of public discussion lately, due to the many advertisements scattered and also the influencers who participate in promoting that Binomo provides huge benefits that are obtained in this Binomo. However, the legality of Binomo in Indonesia is still unclear. In CoFTRA regulation No. 3 of 2019 concerning commodities, Binomo is not included in the subject referred to in article 1. Therefore, this site is illegal. Online Gambling is clearly prohibited and regulated in Article 303 of the Criminal Code (KUHP), Law (UU) Number 7 of 1974, and Government Regulation Number 9 of 1981, and Law Number 11 of 1974, as well as Government Regulation Number 9 of 1981 and Law No. 11 of 2008 (UU ITE). Then what is the Legal Liability for these Binomo traders? Therefore, this research uses normative legal research, namely research that is useful for finding and answering legal issues, the rule of law, legal principles or legal doctrines encountered from a normative perspective and to find out whether the rule of law is in accordance with legal norms. This research is also useful for solving the problems faced. This study uses normative law so as to produce appropriate prescriptions and should be according to law